-24=56-8x

Simple and best practice solution for -24=56-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24=56-8x equation:



-24=56-8x
We move all terms to the left:
-24-(56-8x)=0
We add all the numbers together, and all the variables
-(-8x+56)-24=0
We get rid of parentheses
8x-56-24=0
We add all the numbers together, and all the variables
8x-80=0
We move all terms containing x to the left, all other terms to the right
8x=80
x=80/8
x=10

See similar equations:

| 225(3.50)=x | | 3(25-21r)=48 | | -98=y/2 | | y=2*(-4)+6 | | 1=2v–3 | | 30x-15=180 | | Y-4y=2 | | 8(m+2)=5m+5 | | 75x=36 | | 2+6.5l=34 | | -4(x-3)=-4x | | B/h=2/3 | | -32=y+6 | | 3(y+3)+5y=4(y+1)+17 | | 8x-5=12x=1 | | a2+11a+18=0 | | 5x-12-3x+19=-6 | | b=2=3 | | 5(5x+1)-2x+3=1 | | 5x+12=3-x | | j+-13=27 | | -3(-5x-4)=2 | | y=3*5+2 | | 2x-5(x-3)=4x+1 | | -6(8x-4)+3x=2 | | 3/4x-9=0 | | 5x-12=3-x | | 12+n=14 | | 6x+5-12x=7x+9-19x | | 6-2(8x-8)=1 | | 2(2y-5)+y=7-2+2y | | 5=0.5p |

Equations solver categories